HUBUNGAN DUKUNGAN SOSIAL SUAMI DENGAN DEPRESI PADA IBU POSTPARTUM SAAT PANDEMIC COVID - 19 DI PUSKESMAS KECAMATAN PASAR REBO JAKARTA TIMUR - Jyhan Aprilia Audyna, (2021)
Maternal mental health is a condition that is vulnerable to occur in pregnant women and postpartum mothers. Postpartum depression is a mental illness in pregnant women that appears 2-4 weeks after the mother gives birth. One of the factors that influence postpartum depression is the husband's social support factor. Husband's social support is a form of support from husband to wife whose goal is a wife who has problems feeling cared for by her husband, getting support, feeling loved and appreciated by her husband. This study aims to determine the relationship between husband's social support and depression in postpartum mothers at the Pasar Rebo District Health Center, East Jakarta. Researchers used quantitative research methods with a cross-sectional research design to connect the variables in this study. The sampling technique used is non-probability sampling with a total sample of 99 postpartum mothers. The instruments used were the Social Provision Scale (SPS) Questionnaire to measure husband's social support and the Edinburgh Postpartum Depression Scale (EPDS) Questionnaire to measure depression in postpartum mothers. The results of the chi square test showed that there was a significant relationship between husband's social support and depression in postpartum mothers during the covid-19 pandemic at the Pasar Rebo sub-district health center, East Jakarta and the p value of 0.001 (p < 0.05) on the bivariate husband's social support variable. with depression in postpartum mothers. For mothers who are identified as Postpartum Depression, they can be referred or consulted with a Psychiatrist or a Maternity Nursing Specialist and a Mental Nursing Specialist.